Pembagian Waris Suku Bugis Ditinjau Dari Hukum Adat Dan Hukum Islam - Izdihar Luthfiyyah Surya Gerhana; Elip Intan Pratiwi (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Customary inheritance law is the passing of wealth from the upper generation to their descendants. Inheritance law is based on customary norms, BW, to the Compilation of Islamic Law. The Bugis tribe as adherents of the parental inheritance system still maintain the customary distribution of inheritance Over time and along with the entry of Islam, the Bugis tribe began to use Islamic law as a way out to fulfill the obligations of heirs.